Bacteremia and other body site infection caused by hypervirulent and classic Klebsiella pneumoniae. (March 2017) - Wu, Hua; Li, Dongdong; Zhou, Haijian; Sun, Yunfang; Guo, ling; Shen, Dingxia
Abstract: Objectives: To investigate bacteremia and other body site infection caused by hypervirulent Klebsiella pneumoniae (hvKP), a recently recognized pathogen of invasive infection, and classic Klebsiella pneumoniae (cKP), a very common organism associated with many kinds of nosocomial infection. Methods: Clinical information obtained from patients with both bacteremia and other body site infections caused by hvKP and/or cKP was retrospectively reviewed. Homo-hvKP (or homo-cKP) was defined as homologous hvKP (or cKP) strains from different body sites in each individual patient according to string test, virulence gene amplification and PFGE pattern. MLST was carried on to understand the correlation of sequence type with capsular polysaccharide type for Klebsiella pneumoniae from blood. Results: Sixty-four hvKP and 101 cKP strains were isolated from blood and other body sites of 76 patients who had bacteremia accompanied by other site infection. Among these patients, 27 were infected with homo-hvKP, 32 were with homo-cKP, 12 were with heterogeneous cKP, and five were with both hvKP and cKP. Patients with bacteremia and liver abscesses caused by homo-hvKP accounted for 51.9%, and 92.6% of homo-hvKP infected patients did not receive any invasive procedures before bacteremia. However, patients with bacteremia and biliary tract infection caused by homo-cKP accounted for 34.4%, and 78.1% of homo-cKP infected patients had history of invasive procedures before bacteremia. More homo-hvKP strains (59.3%) than homo-cKP strains (34.4%) were isolated from blood earlier than other sites. HvKP strains were statistically more susceptible to the tested antimicrobials than cKP strains. An outbreak of carbapenem-resistant cKP infection and possible gene transfer of KPC-2 from cKP to hvKP were brought to notice. Conclusions: Both hvKP and cKP could cause bacteremia and other body site infection. But patients with hvKP bacteremia usually suffered from liver abscess without previous invasive procedures, most patients with cKP bacteremia had history of invasive medical procedures. Highlights: HvKP bacteremia came from the origin usually had no previous invasive operation. Most patients with cKP bacteremia had history of invasive medical procedures. CKP bacteremia often originated from infection of biliary tract, pancrease and lung. HvKP were isolated from blood earlier than cKP. Pulmonary infections related to hvKP were next to liver abscesses.